PENGARUH MODAL KERJA DAN BIAYA OPERASIONAL TERHADAP PROFITABILITAS (Jurnal Akuntansi, 2018)
In making a profitability decision, of course the company must have sufficient capital to finance operations in the company. This is to see how the influence of working capital and operational costs on profitability. The research method used by researchers is the method of multiple linear regression analysis, the coefficient of determination test, also performed a classic assumption test that is the Normality, Multicollinearity, Heteroscedasticity and Autocorrelation Tests and also the Hypothesis Test which consists of the F Test and the t Test.Based on the t test (partially) it can be seen that working capital has a significant effect on profitability. Whereas Operational Costs do not affect the profitability. And based on the F Test the value of Fcalculates that working capital and operational costs affect profitability.Â